2020
DOI: 10.2196/15797
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Shame on Patients With Social Anxiety Disorder in Internet-Based Cognitive Behavioral Therapy: Randomized Controlled Trial

Abstract: Background Prior research has demonstrated the efficacy of internet-based cognitive behavioral therapy (ICBT) for social anxiety disorder (SAD). However, it is unclear how shame influences the efficacy of this treatment. Objective This study aimed to investigate the role shame played in the ICBT treatment process for participants with SAD. Methods A total of 104 Chinese participants (73 females; age: mean 24… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Ten studies investigated the effectiveness of internet-based programmes for people with anxiety, depression, trauma, and ADHD. Two RCTs (Lin et al, 2020 ; Wang et al, 2020 ) and two non-RCTs (Chen et al, 2020 ; Kishimoto et al, 2016 ) tested internet-based cognitive behavioural therapy (ICBT) for social anxiety. All four studies showed ICBT reduced the severity of social anxiety, with up to 42% of participants in one study (compared to 20% of participants in the control group; Lin et al, 2020 ) showing significant improvements in social anxiety symptoms post-treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies investigated the effectiveness of internet-based programmes for people with anxiety, depression, trauma, and ADHD. Two RCTs (Lin et al, 2020 ; Wang et al, 2020 ) and two non-RCTs (Chen et al, 2020 ; Kishimoto et al, 2016 ) tested internet-based cognitive behavioural therapy (ICBT) for social anxiety. All four studies showed ICBT reduced the severity of social anxiety, with up to 42% of participants in one study (compared to 20% of participants in the control group; Lin et al, 2020 ) showing significant improvements in social anxiety symptoms post-treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Results showed a 44% improvement rate for participants in the intervention group using the TKS Scale. Another RCT study (Wang et al, 2020 ) explored the effects on reducing shame, a potential mediator of social anxiety. Both guided and unguided internet-based programmes reduced shame proneness compared to the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, in the adult population, research shows a significant efficacy of both self-help iCBT and guided iCBT in anxiety reduction in individuals diagnosed with a social anxiety disorder (Wang et al, 2020b) and of mindfulnessbased online interventions (Questret, Cropley, & Fife-Schaw, 2018;Segal et al, 2020). Finally, Lindegaard and colleagues (2020) investigated the differences in online interventions' efficacy based on cognitive-behavioral and psychodynamic approaches (Lis, Parolin, Calvo, Zennaro, Meyer, 2007;Benzi, Milesi, & Parolin, 2021); researchers found no differences regarding their effectiveness, but both treatments significantly reduced anxiety symptoms.…”
Section: Italiamentioning
confidence: 96%
“…Overall, in the adult population, research shows a significant efficacy of both self-help iCBT and guided iCBT in anxiety reduction in individuals diagnosed with a social anxiety disorder (Wang et al, 2020b) and of mindfulness-based online interventions (Questret, Cropley, & Fife-Schaw, 2018;Segal et al, 2020). Finally, Lindegaard and colleagues (2020) investigated the differences in online interventions' efficacy based on cognitive-behavioral and psychodynamic approaches (Lis, Parolin, Calvo, Zennaro, Meyer, 2007;Benzi, Milesi, & Parolin, 2021); researchers found no differences regarding their effectiveness, but both treatments significantly reduced anxiety symptoms.…”
Section: Introductionmentioning
confidence: 96%